Economics of dairy farming under livestock credit programme of BKB in a selected area of Mymensingh District - Mian, M.R.U.; Halim, M.A.; Jabbar, M.A. (2001)
The costs, returns, and profitability of dairy farming under the livestock credit programme of the Bangladesh Krishi Bank (BKB) were assessed. The amount of loan disbursed and its repayment were also examined. Data for the year 1997-98 were obtained from a total of 40 dairy farms (consisting of small, medium, and large farms). The total cost of dairy farming was found to be highest in medium farms followed by large and small farms, and the highest gross return was found in small farms, followed by medium and large farms. A similar association was found between farm size and net return, implying a negative relationship between farm size and profitability. The amount of loan disbursed per cow was highest in large farms followed by medium and small farms, while the reverse of this order was found in loan repayment. It was also found that dairy farming under the livestock credit programme of BKB faced various constraints like inadequate supply of feed and fodder, unavailability of grazing land, inadequate veterinary services, high transaction cost, and complex procedure of loan disbursement.